A disgraceful tale of déjà vu: New Zealand’s repeated health and safety failures - Barton, Francois; Beaglehole, Toby (New Zealand Journal of Health and Safety Practice, 2024)
In August 2023, the Business Leaders’ Health and Safety Forum (the “Forum”) published its inaugural State of a Thriving Nation (Eaqub, 2023) report. While many of those working closely with the health and safety system in New Zealand may not have been surprised by the report’s key findings – the 4.4 billion annual cost of New Zealand’s health and safety performance and how we’re continuing to drag behind comparable nations such as Australia and the UK in terms of worker harm rates – it caused many to stop and consider exactly what is going wrong in Aotearoa.